The Economics of Volunteering. Measurement Techniques and Labour Outcomes. - Golman, Matias Alejandro (2021)
This dissertation aims to explore volunteering from an economic point of view. As with many non-market activities, volunteers’ contributions to society have been historically underestimated. The research agenda entails an in-depth literature review of measurement methods of volunteers’ economic value, individuals’ motivations to undertake volunteer activities, and potential private benefits obtained from them. Further, two empirical analyses are provided: using the UK Household Longitudinal Study, the economic value of volunteering activity is computed, by using diverse methodological approaches. In addition, an econometric estimation of the long-term volunteering impact on wage levels is presented. The ultimate goal of this dissertation is to generate preliminary conceptual and empirical input for further and more comprehensive PhD research on volunteer work.